1989
DOI: 10.1099/00221287-135-6-1625
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Axial Filaments of Treponema hyodysenteriae by SDS-PAGE and Immunoblotting

Abstract: Purified axial filaments from eight serotypes of Treponema hyodysenteriae and two nonpathogenic intestinal spirochaetes were characterized by SDS-PAGE and Western blotting. Axial filaments of all ten strains had similar SDS-PAGE profiles; five major axial filament polypeptides were identified, with molecular masses of 43.8, 38, 34.8, 32.8 and 29.4 kDa. Hyperimmune gnotobiotic pig serum raised against purified axial filaments of strain P 18A (serotype 4) cross-reacted with all other serotypes and with the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
1
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 29 publications
2
46
1
1
Order By: Relevance
“…hyodysenteriae endoflagella antigens into E. coli with the purpose of identifying protective antigens for vaccine development and confirmed the protective activity of the cloned endoflagella antigen using CF1 mice. However, the antibacterial activity of hyperimmune pig serum raised against axial filaments consisting of 37-, 34-, and 32-kDa proteins could not be demonstrated [10]. On the other hand, pigs that have been infected with virulent strains of B.(S.)…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…hyodysenteriae endoflagella antigens into E. coli with the purpose of identifying protective antigens for vaccine development and confirmed the protective activity of the cloned endoflagella antigen using CF1 mice. However, the antibacterial activity of hyperimmune pig serum raised against axial filaments consisting of 37-, 34-, and 32-kDa proteins could not be demonstrated [10]. On the other hand, pigs that have been infected with virulent strains of B.(S.)…”
mentioning
confidence: 92%
“…The supernatant was taken after centrifugation at 15,000 × g for 30 min and was used for SDS-PAGE. Immunoblotting technique was carried out essentially as previously described [10,13] using semidry type blotter (Sartblot II-S, Sartorius AG, Germany). Treatment with proteinase K was carried out as previously described [18].…”
mentioning
confidence: 99%
“…Convalescent serum of a pig affected with dysentery also reacted strongly with the periplasmic flagella of B. hyodysenteriae P18A. These results mentioned above demonstrated that the periplasmic flagella of B. hyodysenteriae were major antigens in the spirochete [7], but there are no reports on the immunochemical characteristics of proteins of B. alvinipulli. In this study we analyzed the proteins immunochemically and compared the antigens with those of the other Brachyspira species.…”
mentioning
confidence: 67%
“…Many studies on the antigens of B. hyodysenteriae have been published [7,9,11,13,19]. Amongst the reports, a 45-kilodaltons (kDa) polypeptide located in the outer envelope of B. hyodysenteriae P18A is more interesting, because it has the ability to produce antibody in gnotobiotic pig serum [13].…”
Section: Brachyspira (Bmentioning
confidence: 99%
See 1 more Smart Citation